Sustainable Development Program: Synergism Integrated Farming System Implementation in Tambrauw, West Papua with A Holistic Approach - Gracella Theotama; Yesaya Brian Syahputra (Jurnal Indonesia Sosial Sains, 2024)
Indonesia, as an agricultural country with abundant natural resources, still faces the problem of poverty in various regions, especially in West Papua. The high poverty rate in this area is related to the low access to education, food security, and proper economic resources. In an effort to address these issues, the Integrated Farming System (IFS) is considered a potential solution to improve community welfare and support the Sustainable Development Goals (SDGs) targets. This study aims to identify the benefits, challenges and opportunities of IFS implementation in Tambrauw Regency, West Papua, with a focus on its contribution to the achievement of the five SDGs targets, including poverty and hunger alleviation, and improvement of quality of life and environment. The method used in this research is a descriptive qualitative study through literature review and secondary data analysis. Data were taken from various sources such as scientific journals, books, and official documents relevant to the research topic. The results show that the implementation of IFS in Tambrauw has the potential to increase agricultural and livestock productivity, create new jobs, and promote sustainable food production. In addition, the use of organic fertilizers and a holistic approach can have a positive impact on the environment and local communities. IFS is an effective program in supporting the achievement of SDGs through empowerment of local communities and sustainable use of existing resources. However, further support in the form of technological innovation and sustainable government policies are needed to ensure the long-term success of this program.